2020
DOI: 10.1002/jmri.27479
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Hyperintensities Quantification in Healthy Adults: A Systematic Review and Meta‐Analysis

Abstract: Background Although white matter hyperintensities (WMH) volumetric assessment is now customary in research studies, inconsistent WMH measures among homogenous populations may prevent the clinical usability of this biomarker. Purpose To determine whether a point estimate and reference standard for WMH volume in the healthy aging population could be determined. Study Type Systematic review and meta‐analysis. Population In all, 9716 adult subjects from 38 studies reporting WMH volume were retrieved following a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 74 publications
2
13
0
Order By: Relevance
“…The WMH and WM-hypointensity volumes in the participants at baseline were highly similar to findings of older adults within the same age range using the same type of scans and WMH delineation methods [44,45], as well as in published longitudinal studies on physical activity and exercise [24,26]. Moreover, the Generation 100 participants had the expected increase in WMH volume with time.…”
Section: Discussionsupporting
confidence: 70%
“…The WMH and WM-hypointensity volumes in the participants at baseline were highly similar to findings of older adults within the same age range using the same type of scans and WMH delineation methods [44,45], as well as in published longitudinal studies on physical activity and exercise [24,26]. Moreover, the Generation 100 participants had the expected increase in WMH volume with time.…”
Section: Discussionsupporting
confidence: 70%
“…Obviously, counting analysis (visual rating scales or automatic detection) remains inferior to quantitative methods. For example, many studies on WMH-confirmed volumetric measurements were more reliable and objective compared with the visual rating scale, especially in longitudinal studies (23,24). Detailed evaluation for volume of CMBs by these new methods may provide vital information on the etiology, progression, and prognosis of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…White matter hyperintensities are radiological signs of SVD and brain frailty (Group, 2015 ; Melazzini et al, 2021b ) and are associated with a twofold increased risk of dementia and a threefold increased risk of stroke (Debette & Markus, 2010 ). Moreover, WMHs are linked to a faster decline in global cognitive performance, executive function and processing speed (Debette & Markus, 2010 ).…”
Section: Discussionmentioning
confidence: 99%